Differences in the Measurement of Cultural Distance as Determinants of Choice in Foreign Market Entry Modes - Mroczek-Dąbrowska, Katarzyna Dagmara (Studia Oeconomica Posnaniensia, 2015)
Determinants of choice regarding foreign market entry modes are one of the most commonly discussed issues within the field of international business. Factors which affect the process of internationalisation can be traced to various aspects; including the characteristics of the company itself, its location, the home and target markets and, ultimately, the specifics of the industry in which the firm operates. Since the 1980s, entry mode research has often included an analysis of the cultural distance. This analysis seeks to determine whether differences in the way of handling business and in the organizational culture of companies in the home country and in the target market have an impact on the way companies enter foreign markets. A significant problem is the issue of measuring cultural distance, which can be based on a variety of measures. The purpose of this article is to analyse the possible ways of cultural distance operationalization and to apply them to determining cultural distance between Poland and selected economies.